Histopathological study of thyroid lesions in a tertiary care center in coastal belt of South India - Dr. K.F. Magdalene; Dr. Jose Swetha; Dr. Navya Narayanan O; Dr. B Sumangala (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Significant information regarding the lesions of thyroid can be obtained by histopatholological examination of the thyroidectomy specimens. Hence a scrupulous and methodical examination of the thyroidectomy specimens is needed. The aim of present study is to determine the prevalence of thyroid lesions in thyroidectomy specimens.Method: About 240 thyroidectomy specimens received in the pathology department between February 2010 to January 2016 were included in the study. The lesions were basically classified into non- neoplastic and neoplastic. Percentages and simple frequency tables were used for data analysis.Result: Out of the 240 thyroidectomy specimens 214 (89.2%) were from females and 26 (10.8%) were from males. The female: male ratio was 8.2:1. The age of the patients ranged from 2 to 83 years with a mean age of 44.6 years. 160 cases (66.7%) cases were non-neoplastic and 80 cases (33.3%) cases were neoplastic. The common non-neoplastic lesions were colloid goiter (101 cases; 42.1%) and Nodular Hashimoto thyroiditis (28 cases;11.7%). There were 22 benign tumors and 58 malignant tumors. Follicular adenoma was the most common benign tumor (18cases, 7.5%) and Papillary carcinoma was the most common malignant tumor (46 cases, 19.2%).Conclusion: Neoplastic and non- neoplastic disorders affect thyroid gland. Most of the lesions are non- neoplastic. Colloid goiter was the most common non- neoplastic lesion. The most common benign tumor was Follicular adenoma and the most common malignant tumor was papillary carcinoma. This study differs from other studies by an increased incidence of Nodular Hashimoto thyroiditis.